Guide to Good Practice in the Management of Time in Complex Projects. - Building), CIOB (Chartered Institute of (John Wiley & Sons, 2010)
Delayed completion affects IT, process plant, oil and gas, civil engineering, shipbuilding and marine work contracts. In fact it affects all industries in all countries and the bigger the project, the more damage delayed completion causes to costs, to reputation and sometimes, even to the survival of the contracting parties themselves. In simple projects, time can be managed intuitively by any reasonably competent person, but complex projects cannot and a more analytical approach is necessary if the project is to succeed. Although much has been written about how to apportion liability for dela.